Psychological And Pedagogical Patterns of The Process of Comprehension and Comprehension of Educational Material by Students (Eurasian Scientific Herald, 2024)
The article has a psychological and pedagogical character of the process of comprehension and understanding of educational material by students and tells about the processes of cognition and understanding of educational material by students.